Answer:
Question:
x+y+z=3; x-y+z=1; x+y-2z=0
Step-by-step explanation:
-----» Given equation can be written as..
(1)x +(1)y+ (1)z =3
(1)x- (1)y+ (1)z =1
(1)x+ (1)y- (2)z =0
Step 1: We have To calculate D

=1[(-1)(-2)-(1)(1)]-1[(1)(-2)-(1)(1)]+1[(1)(1)-(-1)(1)]
=1[2-1] -1[-2-1] +1[1+1]
=1(1) -1(-3) +1(2)
=1+3+2
<h3><u>D=</u><u>6</u></h3>
______________________________________
Step 2: We have to calculate Dx!!

=3[(-1)(-2)-(1)(1)] -1[(1)(-2)-(1)(0)]+1[(1)(1)-(-1)(0)]
=3(2-1) -1(-2-0) +1(1-0)
=3(1) -1(-2) +1(1)
=3+2+1
<h3><u>DX=</u><u>6</u></h3>
<u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u>
Step 3: We have to calculate Dy!

=1[(1)(-2)-(1)(0)]-3[(1)(-2)-(1)(1)]+1[(1)(0)-(1)(1)]
=1(-2-0)-3(-2-1)1(0-1)
=1(-2)-3(-3)1(-1)
= -2+ 9- 1
<h3><u>Dy=</u><u>6</u></h3>
______________________________________
Step4: we have to calculate Dz!!

=1[(-1)(0)-(1)(1)] -1[(1)(0)-(1)(1)] +3[(1)(1)-(-1)(1)]
=1(0-1) -1(0-1) +3(1+1)
=1(-1)-1(-1)3(2)
=-1+1+6
<h3><u>Dz=</u><u>6</u></h3>
______________________________________
Now, By Cramer's Rule~~



<h3>
<u>x=</u><u>1</u><u> </u><u> </u><u>y=</u><u>1</u><u> </u><u> </u><u>z</u><u>=</u><u>1</u>!!</h3>
Hope it helps!!